Empowering HOTS Through Web-Based Independent Learning: The Mediating Effects of Self-Efficacy and Self-Concept - Refika Andriani; Akhsanul In’am; Adolf Bastian; Andi Idayani; Destina Kasriyati (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Background: This study investigates the effect of web-based independent learning (WBIL) on students’ higher-order thinking skills (HOTS), with self-efficacy (SE) and self-concept (SC) as mediating variables, within the context of translation learning in higher education. Methodology: A quantitative research design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 55 undergraduate students enrolled in translation-related courses through validated instruments measuring WBIL, SE, SC, and HOTS. Findings: The findings indicate that WBIL has a significant positive effect on both self-efficacy and self-concept. Furthermore, both SE and SC significantly predict students’ HOTS, with self-efficacy emerging as the stronger predictor. Mediation analysis reveals that SE and SC partially mediate the relationship between WBIL and HOTS, indicating that WBIL enhances higher-order thinking skills both directly and indirectly through psychological mechanisms. This study contributes to the literature by providing empirical evidence of the WBIL–HOTS relationship specifically within translation learning, a context that requires complex cognitive processes such as analysis, evaluation, and creative decision-making. Unlike prior studies that primarily focus on general digital learning or STEM contexts, this research highlights the role of psychological factors in shaping higher-order thinking in language-based disciplines. Conclusion: The findings underscore the importance of integrating learner autonomy and psychological readiness in designing effective web-based learning environments for translation education. Originality: This study provides empirical evidence of the WBIL–HOTS relationship specifically within translation learning, a context requiring complex cognitive processes. Unlike prior studies focusing primarily on general digital learning or STEM contexts, this research highlights the crucial role of psychological factors in shaping higher-order thinking in language-based disciplines.